Mechanical Properties of Natural Jute Fabric/Jute Mat Fiber Reinforced Polymer Matrix Hybrid Composites. (1st October 2012) - Elbadry, Elsayed A.; Aly-Hassan, Mohamed S.; Hamada, Hiroyuki
Abstract : Recycled needle punched jute fiber mats as a first natural fiber reinforcement system and these jute mats used as a core needle punched with recycled jute fabric cloths as skin layers as a second natural fiber reinforcement system were used for unsaturated polyester matrix composites via modifying the hand lay-up technique with resin preimpregnation into the jute fiber in vacuum. The effect of skin jute fabric on the tensile and bending properties of jute mat composites was investigated for different fiber weight contents. Moreover, the notch sensitivity of these composites was also compared by using the characteristic distanced o calculated by Finite Element Method (FEM). The results showed that the tensile and flexural properties of jute mat composites increased by increasing the fiber weight content and by adding the jute fabric as skin layers. On the other hand, by adding the skins, the characteristic distance decreased and, therefore, the notch sensitivity of the composites increased. The fracture behavior investigated by SEM showed that extensive fiber pull-out mechanism was revealed at the tension side of jute mat composites under the bending load and by adding the jute cloth, the failure mode of jute mat was changed to fiber bridge mechanism.